A brief study on different operating system (International Journal of Engineering and Computer Science, 2015)
this paper presents a comparative study of various operating system archetypes similar to Windows, Linux, UNIX, ANDROID, andAMIGA which are the most well known operating systems. The basic criterion for studying the different operating systems the fundamentalarchitecture power management, Architecture, security and throughput, this research study gives an overview on the similarities and differencesin the basic operating systems use. As every operating system has difference in the underlying composition and working background this givesthe best valuable comparative study.